Innovative Capacity in Muslim-Majority Countries: Does Islamic Finance Play a Role? - Ismail Aremu Muhammed (Journal of Islamic Monetary Economics and Finance, 2025)
The paper examines the influences of Islamic finance and overall financial development on innovative capacity of Muslim-majority nations. It employs a panel dataset comprising 15 Muslim-majority countries over the period 2016-2022. Innovative capacity is measured by the number of patent applications, decomposed into applications made by residents and non-residents. Employing the Feasible GLS technique and taking into account the presence of heteroskedastic and serially correlated errors, we find that the development of Islamic finance is vital for innovations. More specifically, we find robust evidence suggesting that Islamic finance positively affects innovations by non-residents while it has no influence on innovations by residents. Furthermore, overall financial development also significantly influences innovations by non-residents but not innovation by residents. Moreover, there is evidence that trade openness and foreign direct investment positively influence innovations and natural resource rents exert negative impact on innovations. The study concludes that financial system policies that encourage the awareness, accessibility, and depth of Islamic finance operations are needed to boost innovative capacity. Awareness campaign and policies aimed at developing technical education in these countries should be pursued to boost the innovative capacities of residents, which is considerably lower when compared to innovative activities from abroad.